A systematic review and meta-analysis on delaying surgery for urothelial carcinoma of bladder and upper tract urothelial carcinoma: Implications for the COVID19 pandemic and beyond - Leow, Jeffrey J.; Tan, Wei Shen; Tan, Wei Phin; Tan, Teck Wei; Chan, Vinson Wai-Shun; Tikkinen, Kari A. O.; Kamat, Ashish; Sengupta, Shomik; Meng, Maxwell V.; Shariat, Shahrokh; Roupret, Morgan; Decaestecker, Karel; et al. (Frontiers in Surgery, 2022)
PURPOSE: The COVID-19 pandemic has led to competing strains on hospital resources and healthcare personnel. Patients with newly diagnosed invasive urothelial carcinomas (of bladder [UCB] or upper tract [UTUC]) may experience delays to definitive radical cystectomy (RC) or radical nephro-ureterectomy (RNU). We evaluate the impact of delaying definitive surgery on survival outcomes for invasive UCB and UTUC. METHODS: We searched for all studies investigating delayed urologic cancer surgery in Medline and Embase up to June 2020. A systematic review and meta-analysis was performed. RESULTS: We identified a total of 30 studies with 32,591 patients. Across 13 studies (n=12,201), a delay from diagnosis of bladder cancer/TURBT to RC was associated with poorer overall survival (HR 1.25, 95% CI: 1.09-1.45, p=0.002). For patients who underwent neoadjuvant chemotherapy before RC, across the 5 studies (n=4316 patients), a delay between neoadjuvant chemotherapy and radical cystectomy was not found to be significantly associated with overall survival (pooled HR 1.37, 95% CI: 0.96-1.94, p=0.08). For UTUC, 6 studies (n=4,629) found that delay between diagnosis of UTUC to RNU was associated with poorer overall survival (pooled HR 1.55, 95% CI: 1.19–2.02, p=0.001) and cancer-specific survival (pooled HR of 2.56, 95%CI: 1.50-4.37, p=0.001). Limitations included between-study heterogeneity, particularly in the definitions of delay cut-off periods between diagnosis to surgery. CONCLUSIONS: A delay from diagnosis of UCB or UTUC to definitive RC or RNU was associated with poorer survival outcomes. This was not the case for patients who received neoadjuvant chemotherapy.